Evaluating the effectiveness of Kahoot as a gamified tool for teaching English grammar to university students - Samsudin, Asep; Ambawani, Suprih (Politeknik Negeri Jember, 2025)
This study aims to evaluate the effectiveness of using Kahoot as a learning medium for English grammar instruction. With the increasing integration of technology in education, gamified learning platforms like Kahoot have gained popularity for enhancing student engagement and motivation. However, its effectiveness in improving grammar comprehension remains to be thoroughly examined. This research employs a mixed-methods approach, combining quantitative data from pre-test and post-test results with qualitative feedback from student surveys and teacher observations. The participants consisted of secondary school students (or university students, depending on your research sample) who used Kahoot for grammar exercises over a specified period. The findings indicate whether Kahoot significantly improves grammar mastery, student participation, and learning motivation compared to traditional methods. The results also highlight challenges, such as technical issues and varying student proficiency levels, that may affect its implementation. This study provides valuable insights for educators considering Kahoot as a supplementary tool for grammar instruction and suggests recommendations for optimizing its use in the classroom.